Application of Information Technology for Studying Conservation of Local Wisdoms in the Area of Muang Kaen Pattana Municipality, Mae Taeng District, Chiang Mai Province - รัตนชูโชค พรวนา (Community and Social Development Journal, 2016)
The research on the topic of “Application of Information Technology for Studying Conservation of Local Wisdoms in the Area of Muang Kaen Pattana Municipality, Mae Taeng District, Chiang Mai Province” was based on these following objectives: to collect local wisdom data; to create some learning materials regarding conservation of local wisdoms via the participatory process involving the community’s students and the researchers; to distribute the learning materials via the internet for the community’s students; and to assess achievements from utilizing the learning materials. The sample group used in this study comprised the group of 19 local wisdom informants. The group of 22 system model and local wisdom media model designers, and the group of 53 system evaluators. Data were collected using interviews, public discussion forums, questionnaires, and the pre-test and post-test technique. After that, the collected data were analyzed using statistical analysis, such as frequency, percentage, and t-test. The research collected data regarding local wisdoms in the area, which included the wisdoms about Kone Noi mushroom (Coprinus fimetarrius) cultivation, the traditional 700-year lamp event, traditional waterwheels, traditional Lanna rites, calligraphy with traditional Northern texts, elephant sculpture made by mulberry paper, knife making, and Jor Tong (banana leaves) handicraft. In addition, the research created an information system for gathering the local wisdom data into the system. The learning materials regarding local wisdom conservation were developed to be used for managing learning of the community’s students. The information system helped disseminate the knowledge derived from studying the participatory conservation of local wisdoms via the internet. This is considered an efficient approach for sustainable conservation of local wisdoms . The research also conducted a survey to assess satisfaction of the target groups in 2 schools and the group of local wisdom informants toward the information system that they had used. According to the survey results, it was found that the users had a high level of satisfaction. Furthermore, the study results regarding research utilization based on pre-test and post-test achievements of the students from both schools revealed that their mean post-test score after learning with the materials increased from their pre-test score for 57.27%. The student also revealed the students progress at the significance level of 0.05 The student score obtained from the post-test were higher that those from the pre-test.